Thermodynamic study of N-acetyl glycine in aqueous tetraethylammonium iodide solutions in the temperature interval (288.15 to 308.15) K: Volumetric and acoustic study. (March 2016) - Sharma, Suresh Kumar; Singh, Gurpreet; Kumar, Harsh; Kataria, Ramesh
Highlights: New data on volumetric and acoustic studies of N-acetyl glycine in aqueous TEAI solutions. (Solute + solvent) interactions increase with the increase in concentration of co-solute. (Ion + hydrophobic) and (hydrophobic + hydrophobic) interactions are dominant at higher temperatures. N-acetyl glycine behaves as structure-maker in aqueous TEAI solutions. Abstract: Knowledge of thermodynamic properties of substituted amino acids in aqueous medium can provide valuable information regarding the stabilisation mechanism of proteins. In this study, we report the density and ultrasonic speeds of N-acetyl glycine in (0.03, 0.05, 0.1, 0.15 and 0.2) mol ⋅ kg −1 aqueous solutions of tetraethylammonium iodide (TEAI) at temperatures (288.15, 293.15, 298.15, 303.15 and 308.15) K and at pressures 101 kPa. From these results, the apparent molar volume and acoustical parameters, coefficient of isentropic compression, molal hydration number and apparent molar isentropic compression have been evaluated. The partial molar volume, partial molar isentropic compression, and their corresponding transfer functions were calculated. These results were used to interpret the type of interactions occurring in the ternary mixtures using the co-sphere overlap model. The pair and triplet interaction coefficients have been calculated from both the properties. The concentration and temperature dependence of (solute + solute) and (solute + solvent) interactions in the present study was also discussed. The partial molar volumes were used to obtain the partial molar isobaric expansibilities for N-acetyl glycine to examine the temperature dependence of such interactions. The structure-making/breaking ability of N-acetyl glycine has also been discussed in terms of the sign of ∂ C P, ∅ 0 ∂ P T .